Methods for isolating, expanding, and characterizing umbilical cord mesenchymal stromal cells and their in vitro metabolism - Smith, Joseph Robert (Kansas State University, 2017)
Mesenchymal stromal cells (MSCs) derived from the umbilical cord (UC-MSCs) have therapeutic applications and are studied to understand their potential uses and immunomodulatory properties. Research must identify good manufacturing process (GMP) compliant methods to isolate and expand UC-MSCs. In addition, MSCs metabolism characteristics in culture are unknown, warranting further investigation. Viability of MSCs decreases after cryopreservation, which is detrimental to clinical translation. Previously published methods used to isolate MSCs from the umbilical cord included open dissection steps and xenogeneic components. Here, I developed improved methods by eliminating dissection which reduces contamination risks. Instead, I used the whole umbilical cord and Miltenyi dissociator tubes to mechanically and enzymatically dissociate cells in a closed system. Xenogeneic components were decreased by using medium containing pooled human platelet lysate instead of fetal bovine serum. The cell numbers isolated from umbilical cord averaged 2.68 x 10⁵ per cm, which represents greater than 20 fold improvement over the previous method. Moreover, expansion cell numbers were increased using 10% pooled human platelet lysate supplemented media. The UC-MSCs generated here met the International Society of Cell Therapy (ISCT) definition of MSCs. Metabolism characteristics of MSCs indicated that glucose was the critical metabolite, maintaining cells longer in culture than glutamine. Cell death followed depletion of glucose, too. Finally, the average viability after thawing cryopreserved MSCs was more than 95%, higher than previous methods. The improvements I introduced to our methodology could speed clinical translation of MSCs as an allogeneic cellular therapy
Keywords: Mesenchymal stromal cells; Stem cells; Umbilical cord; Platelet lysate; Isolation methods; Cryopreservation